Validation of a predictive method for sunscreen formula evaluation using gene expression analysis in a Chinese reconstructed full‐thickness skin model. (1st April 2019) - Liu, Y.; Wang, R.; He, X.; Dai, H.; Betts, R. J.; Marionnet, C.; Bernerd, F.; Planel, E.; Wang, X.; Nocairi, H.; Cai, Z.; Qiu, J.; et al.
Abstract: Objective: This study aimed to establish a predictive in vitro method for assessing the photoprotective properties of sunscreens using a reconstructed full‐thickness skin model. Materials and Methods: A full‐thickness skin model reconstructed with human fibroblasts and keratinocytes isolated from Chinese skin was exposed to daily UV radiation (DUVR). We examined the transcriptomic response, identifying genes for which expression was modulated by DUVR in a dose‐dependent manner. We then validated the methodology for efficacy evaluation of different sunscreens formulas. Results: The reconstructed skin model was histologically consistent with human skin, and upon DUVR exposure, the constituent fibroblasts and keratinocytes exhibited transcriptomic alterations in pathways associated with oxidative stress, inflammation and extracellular matrix remodelling. When used to evaluate sunscreen protection on the model, the observed level of protection from UV‐induced gene expression was consistent with the corresponding protection factors determined clinically and allowed for statistical ranking of sunscreen efficacy. Conclusions: Within this study we show that quantification of gene modulation within the reconstructed skin model is a biologically relevant approach with sensitivity and predictability to evaluate photoprotection products.